Predictive factors for effective salvage therapy of nonseminomatous germ cell tumors of testis - A.Dimopoulos, M.; Amato, R. J.; Logothetis, C. J. (Urology, 1991)
Twenty-four patients with metastatic and chemotherapy-refractorynonseminomatous germ cell tumors of the testis were treated with various chemotherapy regimens upon failure. Eight of the 24 patients (33 %) are alive and disease free after salvage therapy with a median follow-up of sixteen months. Prognostic factors tested included those known to be predictive for initial response to therapy (clinical stage and degree of elevation of the biomarkers). In addition, time to initiation of salvage therapy and response to initial chemotherapy were assessed as variables. Our data suggest that patients with solitary organ metastases following relapse, and response to initial chemotherapy are favorable predictors for response to salvage treatment. All the patients with solitary organ metastases (5/5 [100 %]) but only 3/19 (16 %) of the patients with multiple metastatic sites were salvaged. Patients with delayed initiation of salvage therapy had a reduced likelihood of achieving a complete remission but this was not statistically significant. The variables identified need to be incorporated into future trials testing the efficacy of salvage therapy for patients with nonseminomatous tumors of the testis. © 1991 Cahners Publishing Company.